2006
DOI: 10.1117/12.683343
|View full text |Cite
|
Sign up to set email alerts
|

Tunable optofluidic distributed feedback dye lasers

Abstract: We demonstrated a continuously tunable optofluidic distributed feedback (DFB) dye laser on a monolithic poly(dimethylsiloxane) (PDMS) elastomer chip. The optical feedback was provided by a phase-shifted higher order Bragg grating embedded in the liquid core of a single mode buried channel waveguide. We achieved nearly 60nm continuously tunable output by mechanically varying the grating period with two dye molecules Rhodamine 6G (Rh6G) and Rhodamine 101 (Rh101). Single-mode operation was obtained with <0.1nm li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, the need for the frequent replacement of dye solutions and grating periods severely hampers real-time dynamic tuning in optofluidic dye lasers. Li et al reported a method of continuously stretching and compressing a microfluidic chip on a mechanical stage [ 31 , 32 ]. Nevertheless, the deformation of the entire device using a mechanical stage impedes integration with more complex microfluidic systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the need for the frequent replacement of dye solutions and grating periods severely hampers real-time dynamic tuning in optofluidic dye lasers. Li et al reported a method of continuously stretching and compressing a microfluidic chip on a mechanical stage [ 31 , 32 ]. Nevertheless, the deformation of the entire device using a mechanical stage impedes integration with more complex microfluidic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al reported a method of continuously stretching and compressing a microfluidic chip on a mechanical stage [31,32]. Nevertheless, the deformation of the entire device using a mechanical stage impedes integration with more complex microfluidic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the problem of dye bleaching is accounted for by a continuous convective flow of liquid-dissolved dye molecules, thus compensating the bleaching dynamics caused by the external optical pump. The required, convective dye-replenishing flow has been achieved by external fluid-handling apparatus (syringe pumps), 4, 6-8 on-chip micro-fluidic pumps, 9,10 or by means of capillary effect. 11 In this paper we find supporting evidence that such opto-fluidic devices may potentially be operated for days by diffusion without the need for a convective flow.…”
Section: Introductionmentioning
confidence: 99%